Status of Capybaras (Hydrochoerus hydrochaeris Rodentia: Hydrochaeridae) and Potential for Establishment in Florida - Brandon Parker; C. Jane Anderson; Christina M. Romagosa; Samantha M. Wisely; Daniel Pearson; John Seyjagat; Katherine Ashley Sayler (EDIS)
Would you know what to do if you saw a two-foot-tall, 100-pound exotic rodent strolling through your neighborhood? It’s highly unlikely, but, depending on your location, not absolutely impossible. Capybaras, the world’s largest rodents, are native to South America but have been spotted in the state of Florida and may have potential to establish populations here. This 5-page fact sheet written by Brandon Parker, C. Jane Anderson, Christina Romagosa, Samantha Wisely, Daniel Pearson, John Seyjagat, and Katherine Ashley Sayler and published by the UF/IFAS Department of Wildlife Ecology and Conservation describes capybaras, explains how they got to Florida, and shows where the semiaquatic, herbivorous rodents have been sighted so far. edis.ifas.ufl.edu/uw438